2018
DOI: 10.1107/s1600576718004326
|View full text |Cite
|
Sign up to set email alerts
|

Direct determination of one-dimensional interphase structures using normalized crystal truncation rod analysis

Abstract: A one‐dimensional non‐iterative direct method was employed for normalized crystal truncation rod analysis. The non‐iterative approach, utilizing the Kramers–Kronig relation, avoids the ambiguities due to an improper initial model or incomplete convergence in the conventional iterative methods. The validity and limitations of the present method are demonstrated through both numerical simulations and experiments with Pt(111) in a 0.1 M CsF aqueous solution. The present method is compared with conventional iterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Since the calculated intensities of the model (c) are 9% each, the experimental observed value of ~3% each is reasonable for the model (c) considering the DW factor. This is also consistent with the CTR measurements [15,16] where the direct inversion technique was used to obtain the Cs + layer density of ~0.7 e − /Å 3 , which is ~25% of 2.7 e − /Å 3 for Pt layer electron density. Under this scenario, the highly disordered hydrated Cs + ions maintain the short-range single-sublattice (2×2) model (c) structure in electrolyte.…”
Section: In-plane Edl Structure On Pt(111) Surfacesupporting
confidence: 87%
See 2 more Smart Citations
“…Since the calculated intensities of the model (c) are 9% each, the experimental observed value of ~3% each is reasonable for the model (c) considering the DW factor. This is also consistent with the CTR measurements [15,16] where the direct inversion technique was used to obtain the Cs + layer density of ~0.7 e − /Å 3 , which is ~25% of 2.7 e − /Å 3 for Pt layer electron density. Under this scenario, the highly disordered hydrated Cs + ions maintain the short-range single-sublattice (2×2) model (c) structure in electrolyte.…”
Section: In-plane Edl Structure On Pt(111) Surfacesupporting
confidence: 87%
“…In this report, we included the water density explicitly in the standard state to provide the overall density modulations with respect to the background electron density of water, 0.33 e − /Å 3 . The normalized data were fit to the four peak model used in the previous EDL study on Pt(111) surface [15], which was derived from the direct inversion method [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were relaxations of Pt(111) surface lattice planes depending on the potentials, as shown in Table S1 . Our preliminary study indicated that the lattice relaxations do not impede our structure determination of Cs + distributions. This is because the lattice relaxations mostly affect intensities near Bragg peaks, (0 0 3) and (0 0 6), whereas the Cs + distributions change the intensities near anti-Bragg regions between the Bragg peaks.…”
mentioning
confidence: 80%
“…However, the long‐proposed Stern layer was finally observed in recent x‐ray study of Pt(111) in alkali fluorides and chlorides . Surprisingly, the Stern layer persists over a wide potential range where the GC models was generally believed to be effective.…”
Section: Electrode Interface Studies With Conventional Surface X‐ray mentioning
confidence: 99%